Comportamento de Ceratocystis sp. in vitro sob diferentes temperaturas, meios de cultura e pH - Santos, Paula Leite dos [UNESP]; Firmino, Ana Carolina [UNESP]; Tozze Júnior, Hugo José; Barros, Susette Aparecida de; Furtado, Edson Luiz [UNESP] (My University, 2011)
The genus Ceratocystis fungus is a cosmopolitan and in Brazil the main species is C. fimbriata, which causes disease in many plants of great economic importance. The study aimed to evaluate the mycelial growth in the media: Oats, BDA, MEA, AA, CE, CEA, and V8-A. For this we used 14 isolates of Ceratocystis from different hosts. The colonies were incubated at 30 ° C under a photoperiod alternating, 25oC, 20oC and 15oC. As for the study on the effect of pH on the mycelial growth of Ceratocystis isolates were used 6. The colonies were incubated in alternating photoperiod (12h) at 25 ° C ± 2. The tests were performed on MEA medium (malt, yeast extract and agar) with different pH ranges: 5, 7 and 9. In all experiments each treatment consisted of four replicates in a randomized design. Evaluations were performed daily until the first contact one of the colonies with the edge of the board, through measurements of diameters of each colony. The means were the CE and CEA that provided better growth to the fungus at all temperatures, since the middle of oats and AA were the fungus had lower growth. The fastest growth was observed in the temperature of 25oC. Most of the isolates did not produce sexual structures through AA. The best growth for isolated eucalyptus and teak was observed in medium with pH 7, while for the isolated cocoa showed no significant difference between the different pH ranges worked.

O gênero Ceratocystis é um fungo cosmopolita sendo que no Brasil a principal espécie é C. fimbriata, causadora de doenças em muitas plantas de grande importância econômica. O trabalho objetivou avaliar o crescimento micelial nos meios: Aveia, BDA, MEA, AA, CE, CEA e V8-A. Para isso foram utilizados 14 isolados de Ceratocystis de diferentes hospedeiros. As colônias foram incubadas sob fotoperíodo alternado a 30oC, 25oC, 20oC e 15oC. Já para o estudo referente ao efeito do pH sobre o crescimento micelial de Ceratocystis foram usados 6 isolados. As colônias foram incubadas em fotoperíodo alternado (12h) a 25oC±2. Os testes foram realizados em meio MEA (Malte, extrato de levedura e Agar) com diferentes faixas de pH: 5, 7 e 9. Em todos os experimentos cada tratamento foi constituído de quatro repetições, em delineamento inteiramente casualizado. Realizaram-se avaliações diárias até o primeiro contato de uma das colônias com a borda da placa, através de mensurações de diâmetros de cada colônia. Os meios CE e CEA foram os que propiciaram melhor crescimento ao fungo em todas as temperaturas, já meio de aveia e AA foram os que o fungo teve menor crescimento. A maior velocidade de crescimento foi observada na temperatura de 25oC. A maioria dos isolados não produziu estruturas sexuais em meio AA. O melhor crescimento para isolados de eucalipto e teca foi observado em meio com pH 7, já para o isolado de cacau não apresentou diferença significativa entre as diferentes faixas de pH trabalhadas.
In vitro Ceratocystis sp. behavior under differents temperatures, culture medium and pH
Keywords: Growth; Mycelium; Characterization; Crescimento; Micélio; Caracterização